PROBLEM ISSUES OF HIV-INFECTION AMONG WOMEN AND CHILDREN THEY GIVE BIRTH TO - V.N. Sadovnikova (Вопросы современной педиатрии)
The work deals with the complex research findings of the morbidity dynamics and HIV-infection prevalence among the pregnant women and risk for its transmission from a mother to a child, as well as the estimate of their regular medical check up, antiretroviral prevention of HIV-infection perinatal transmission, health status of children born to HIV-infected mothers and newly-born children within the general population. The research showed that recent years witnessed the steady increase of HIV-infected pregnant women and children born to them. High risk for HIV-infection perinatal transmission still persists. The article describes the reasons for the low coverage of the antiretroviral prevention among the pregnant women. The author gives an estimate of the associated diseases of the HIV-infected mother and health status of the newly born child. The work shows the necessity in development and implementation of the special prevention measures within the antenatal and postnatal regular medical check up of a mother and a child.Key words: HIV-infected pregnant women and children they give birth to, regular medical check up, health status of mothers and newly born children.